Adolescents' perceived barriers to accessing sexual and reproductive health services in California: a cross-sectional survey - Martha J. Decker; Tara V. Atyam; Catherine Gilmore Zárate; Angela M. Bayer; Consuelo Bautista; Melissa Saphir (BMC, 2021)
Abstract Background Adolescents may forego needed sexual and reproductive health (SRH) services due to a variety of concerns and barriers. The purpose of this study is to compare adolescents' perceptions of these barriers by participant characteristics including race/ethnicity, gender, sexual orientation, housing situation, and sexual experience. Methods Adolescents in a California-wide sexual health education program completed an anonymous survey at baseline (N = 10,015) about perceived barriers to using SRH services. Logistic regression analyses that accounted for the clustered data structure assessed differences by gender, age, sexual orientation, race/ethnicity, living situation, and sexual experience. Results The majority of participants were Hispanic/Latino (76.4%) with an average age of 14.9 years, and 28.8% had sexual experience. Half of the youth reported concerns about test results (52.7%), cost of services (52.0%), and confidentiality of services (49.8%). When controlling for other characteristics, youth identifying as transgender/non-binary/multiple genders had the highest odds of perceiving cost (odds ratio (OR) 1.89) and confidentiality (OR 1.51) as barriers. Increasing age was associated with decreasing odds of all barriers. Sexual orientation was a consistent predictor, with LGBQ+ youth having higher odds of perceiving test results (OR 1.21), cost (OR 1.36), and confidentiality (OR 1.24) as barriers. Asian or Pacific Islander/Native Hawaiian youth had higher odds of perceiving test results (OR 1.68) and cost (OR 1.37) as barriers. In contrast, Black youth had lower odds of reporting cost (OR 0.65) and confidentiality (OR 0.77) as barriers. Younger respondents and youth who identified as female, transgender/non-binary/multiple genders, LGBQ+, and Asian or Pacific Islander/Native Hawaiian had higher odds of reporting five or more barriers compared to reference groups. Conclusions The majority of adolescents face barriers to accessing appropriate SRH services, with females, gender-minority youth, younger adolescents, LGBQ+ youth, and Asian and Pacific Islander/Native Hawaiian youth more likely than others to report barriers. Access to SRH services can be improved through strengthening linkages between clinics and SRH education programs, providing youth-friendly clinical services, and ensuring youth have sufficient information, skills, and support to access care. Trial registration Approved by California Health and Human Services Agency's Committee for the Protection of Human Subjects [12-08-0658, 11/30/2017].